INTEGRATION OF SCIENTIFIC AND EDUCATIONAL UNIVERSITY WORK: EXPERIENCE OF COMPARATIVE ANALYSIS OF THE THERMAL DECOMPOSITION OF Mg(NO3)2 · 6H2O IN AIR AND SUPERHEATED WATER VAPOR - Sergey F. Katyshev; Aleksandr S. Molodykh; Yevgeny A. Nikonenko; Ludmila A. Baikova (Obrazovanie i Nauka, 2016)
Abstract. The aim of the investigation is to select how the thermal decomposition of crystallohydrate magnesium nitrates to capture the nitrogen compounds that are harmful to the environment; for the return of nitric acid to the initial stage of the process. Methods. The methods involve physical and chemical analysis (IR spectroscopy, rentgennofazovy analysis), thermolysis and thermal hydrolysis of magnesium nitrate. Results. Magnitudes of thermal effects are determined; mechanisms of thermal decomposition of magnesium nitrate in air and overheated water vapor are posed. Thermohydrolysis renders possible to produce undiluted magnesium oxide and regenerate nitric acid. Scientific novelty. Undiluted magnesium oxide was produced by the method that requires less energy consumption. Practical significance. The research results on regeneration of nitric acid and its reuse in the raw material processing containing magnesium open new prospects for production and can be applied as course materials for a practical training in organic chemistry in postgraduate study on chemical specialties.